Violations of freedom of conscience and religion in the sphere of religious education in schools (Finding a way out of Poland's rule-of-law crisis: Possible courses of action and reform, 2026)
Chapter seven of the report discusses violations of the freedom of conscience and religion in the sphere of school religious education that occurred as a result of the actions of the Minister of Education, Barbara Nowacka. The author points out that the minister issued regulations governing the organization of religion classes on three occasions, blatantly disregarding the constitutional and statutory requirement to reach an agreement with churches and other religious organizations. These actions – consisting of, among other things, not including the grade for religion in the grade point average and merging students into cross-class groups – were intended to lower the status of the subject and discourage attendance at these classes. All of these regulations were ruled unconstitutional by the Constitutional Tribunal.As part of corrective measures, the author demands the publication of and compliance with the rulings of the Constitutional Tribunal, which will restore the legal state existing prior to the harmful changes. He also advocates for holding those responsible for issuing the defective legal acts accountable through constitutional liability before the Tribunal of State, as well as criminal or disciplinary liability. Additionally, the author points to the need to provide redress to the aggrieved parties, in particular students who suffered discrimination or obstacles, and religion teachers.To permanently safeguard the rule of law, the author advocates supporting a citizens' bill (print no. 1603/10th term). It transfers the rules for organizing religion classes from the level of a regulation to a statute, which will prevent the minister from making unilateral and arbitrary decisions in the future. The bill envisages a return to the previously established consensus, eliminates cross-class groups, and introduces a mandatory choice between religion and ethics.